(untitled) (Swiss Medical Weekly, 2025)
STUDY AIMS: Left atrial appendage occlusion (LAAO) is an accepted alternative stroke prevention strategy for patients with atrial fibrillation (AF) and contraindications to oral anticoagulation despite the lack of randomised data in this population. This study aims to compare the outcomes of LAAO and direct oral anticoagulation (DOAC) therapy in patients with high bleeding risk. METHODS: This cardinality-matched analysis comprised data from the Beat-AF and Swiss-AF cohorts (n = 3960; enrolment from 2010 to 2014 and from 2014 to 2017, respectively), along with the Zurich LAAO Registry (n = 535; patients included between 2010 and 2023). The primary endpoint was a composite of stroke, cardiovascular death or major bleeding. The individual components constituted the secondary endpoints. Time-dependent cumulative incidence curves were constructed and a competing risk analysis was included. RESULTS: After matching, 478 patients with a DOAC score ≥8 and 159 patients with previous major bleeding were compared in a 1:1 and 1:2 ratio, respectively, regarding their stroke prevention strategy (DOAC versus LAAO). After a median follow-up time of 4.9 years (interquartile range [IQR]: 2.2–6.1) in all patients with a DOAC score ≥8 and 4.4 years (IQR: 2.0–6.0) in all patients with previous major bleeding, there were no significant differences in the primary endpoint (hazard ratio [HR]: 0.88, 95% confidence interval [CI]: 0.67–1.14, p = 0.33 and HR: 0.79, 95% CI: 0.50–1.27, p = 0.33) and in the rates of stroke (HR: 0.74, 95% CI: 0.39–1.42, p = 0.36 and HR: 1.09, 95% CI: 0.33–3.62, p = 0.89) and cardiovascular death (HR: 0.97, 95% CI: 0.68–1.38, p = 0.85 and HR: 0.91, 95% CI: 0.50–1.64, p = 0.74). The rate of major bleedings was significantly lower in the LAAO group of both cohorts (HR: 0.55, 95% CI: 0.32–0.94, p = 0.029 and HR: 0.32, 95% CI: 0.13–0.79, p = 0.013). CONCLUSION: In this high bleeding risk population, LAAO was associated with similar effectiveness in preventing atrial fibrillation-related stroke and cardiovascular death and significantly lower rates of major bleeding compared to DOAC therapy. This strengthens the value of LAAO as an alternative stroke prevention strategy for patients at high risk of bleeding.